Student Motivation in Outdoor Recreation Engagement: Examining the Validity and Reliability of the Measuring Instruments - Aziz, Roslizawati Che; Kosnin, Ruzanifah; Hashim, Nik Alif Amri Nik; Abdullah, Fadhilahanim Aryani; Saidin, Siti Salina; Zulkefli, Nor Syuhada; Bakar, Nurzehan Abu (The journal of contemporary issues in business and government, 2021)
Motivation is a detailed, wide-researched concept in the tourism field, and it is often associated with the pull and push factors and their influence on student behaviour. Hence, using a quantitative method through a questionnaire survey, this study aims to measure motivation and its roles in influencing higher education students to engage in outdoor recreation activities. A total of 150 respondents had participated in this study and the data gathered from the questionnaires were analyzed using the IBM SPSS version 26 statistical software. Priorly, expert evaluations were conducted to measure the reliability, content validity, face validity, and normality of the data. The pilot study has verified the reliability of the measuring instrument, while the data evidenced rational normality. Overall, the findings supported the measuring instruments proposed in this study for further research.